COF Scaffold Membrane with Gate-Lane Nanostructure for Efficient Li+/Mg2+ Separation - Zhang, Zixuan; Kong, Yan; Li, Runlai; Yue, Xiaolin; Deng, Hao; Zheng, Yu; Zhang, Sui; Zhang, Runnan; Jiang, Zhongyi (Nano-Micro Letters, 2026)
Due to complex ion–ion and ion–membrane interactions, creating innovative membrane structures to acquire favorable ion mixing effect and high separation performance remains a big challenge. Herein, we design covalent organic framework (COF) scaffold membrane with gate-lane nanostructure for efficient Li+/Mg2+ separation. COF nanosheets, serving as the scaffold, are intercalated by polyethyleneimine (PEI) to form the permeating layer. Subsequently, PEI on the surface reacts with 1,4-phenylene diisocyanate to form the polyurea gating layer. The gating layer, bearing tailored smaller pore size, affords high rejection to co-ions (Mg2+) and thus high Li+/Mg2+ selectivity. The permeating layer, with asymmetric charge and spatial nanostructure for creating individual lanes of Li+ and Cl−, facilitates Li+ transport and thus high Li+ permeability. The optimum COF scaffold membrane exhibits the permeance of 11.5 L m−2 h−1/bar−1 and true selectivity of 231.9 with Li+ enrichment of 120.2% at the Mg2+/Li+ mass ratio of 50, exceeding the ideal selectivity of 80.5 and outperforming all ever-reported positively charged nanofiltration membranes. Our work may stimulate the further thinking about how to design the hierarchical membrane structure to achieve favorable ion mixing effect and break the membrane permeability–selectivity trade-off in chemical separations. Highlights: 1 Covalent organic framework (COF) scaffold membranes with gate-lane nanostructure were prepared. 2 The gating layer affords high rejection to Mg2+ and thus high Li+/Mg2+ selectivity. The permeating layer bearing Li+ lanes and Cl− lanes facilitates Li+ transport and thus high Li+ permeability. 3 The COF scaffold membrane exhibits the true selectivity of 231.9 with Li+ enrichment of 120.2% at the Mg2+/Li+ mass ratio of 50, exceeding the ideal selectivity of 80.5.